Hulled wheat: Proceedings of the first International Workshop on Hulled Wheats, 21-22 July 1995, Castelvecchio Pascoli, Tuscany, Italy - Padulosi, S.; Hammer, K.; Heller, J.; International Plant Genetic Resources Institute; Leibniz Institute of Plant Genetics and Crop Plant Research (1996)
Present day cultivation of einkorn (Triticum monococcum), emmer (T. dicoccum in situ conservation, are briefly considered. (Abstract © CAB ABSTRACTS, CAB International)